Structural dynamic investigation of the mutation-induced resistance mechanisms of Mycobacterium tuberculosis DNA-directed RNA polymerase against Rifampicin - Monama, Mokgerwa Zacharia (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Bioinformatics)
Emerging resistant strains of Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB) disease, continue to plague mankind and reduce the efficacies of antitubercular therapies that have been an effective defence against TB for decades. More specifically, mutations located in the Î² subunit of the multisubunit Mtb RNA replicative machinery, RNA polymerase (RNAP), have been well established as the reason behind resistance to the first-line antitubercular drug rifampicin (RIF), which has resulted in therapeutic failure in several clinical cases. Additionally, elusive details pertaining to the underlying mechanisms associated with RIF resistance due to the presence of Mtb-RNAP-Î² mutations, have resulted in setbacks in the development of novel and effective drugs that might be able to curb the ongoing threat. Hence, in this investigation, we attempted to resolve the involved Mtb-RNAP structural events at the molecular level to discern potentially important details regarding the nine clinically relevant Mtb-RNAP-Î² missense mutations under investigation. Hence, for the first time, we conducted an in-silico RIF resistance investigation using the Mtb-RNAP complex. To accomplish the set-out task, we first employed the use of more traditional post-MD analytical approaches such as root mean square deviation, root mean square fluctuation, radius of gyration, center of mass distance analyses, hydrogen bond occupancies, and binding free energy calculations, to conduct a global analysis of the mutated Mtb-RNAP proteins referencing RIF efficacy. Our findings revealed that the mutations may have a perturbation effect resulting in the disruption of essential structural dynamics attributed to the protein's catalytic functions. This was for instance observed for the Î²fork loop 2 domain, the Î²'zinc-binding domain, the Î²' trigger loop domain, and the Î²'jaw domain, which happen to be in line with previously reported experiments detailing changes in RNAP processivity. Complementarily, some of the mutations more specifically perturbed the RIF binding pocket (RIF-BP) which observably led to the reorientation of RIF from the native or active orientation needed to obstruct the processive addition of nucleoside triphosphates to the growing RNA transcript. The mutation-induced repositioning from the active RIF orientation was also reflected through the loss of essential interactions between RIF and the RIF-BP along with the loss of binding affinities captured for a majority of the mutant proteins. In conjunction with traditional analytical approaches, we further employed computational alanine scanning, weighted contact map analyses, and dynamic residue network (DRN) analyses, a novel approach that delineates residue-residue communication pathways through several metrics, to further elucidate how a set of clinically relevant mutations affect Mtb-RNAP function. With that, we were able to observe several key changes in residue importance and interactions that may be instrumental in bringing about RIF resistance and the compensatory conformational changes we observed among the mt systems through global analysis. Furthermore, we identified persistent hubs that may be particularly important in maintaining transcriptional activities in the presence and absence of the investigated mutations and RIF that could serve as potential resistance markers for future therapeutic investigations. We believe these findings will significantly aid future efforts in the discovery of new treatment options with the potential to overcome antitubercular resistance.
Keywords: Mycobacterium tuberculosis; Rifampin; Drug resistance; Molecular dynamics -- Simulation methods